Effect of trust, convinience, security and quality of service on online purchase decision (consumer case study in tangerang selatan area) - Irawan, Indra Ade (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This study aims to determine the influence of trust, convenience, security, and quality of service to online purchasing decisions on consumers in the area of South Tangerang. The population is all consumers who buy products online in South Tangerang region. The type of data used is the primary data using the questionnaire method. The sampling technique is using non probability sampling with sample of 200 respondents. The analysis technique used is multiple regression. The results showed that: (1) Trust has a positive and significant effect on online purchasing decisions. (2) Convinience has a positive and significant impact on online purchasing decisions. (3) Security has a negative and insignificant effect on online purchasing decisions. (4) Service Quality has a positive and significant impact on online purchasing decisions.